Komplikasi Sindrom Stevens-Johnson (SSJ) dan Nekrolisis Epidermal Toksik (NET) - Aribowo I Kadek; Angel Benny Wisan (Cermin Dunia Kedokteran, 2024)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening mucocutaneous reactions with severe skin involvement; may affect many internal organ systems with significant psychosocial complications. Several studies have documented physical complications associated with Stevens-Johnson syndrome and toxic epidermal necrolysis (TEN). SJS/TEN patients require multidisciplinary care to deal with psychological complications and reduced quality of life.